PENGARUH STRES KERJA TERHADAP KINERJA KARYAWAN PADA PT. BANK PERKREDITAN RAKYAT DANA RAYA MANADO - Agustina Nola Tampi; Riane Jhonly Pio; Dolina Laura Tampi (JURNAL ADMINISTRASI BISNIS, 2017)
Abstrak. Competition and a higher demand in professionalism raises the amount of pressure that an individual faces in their work environment. The effect of anxiety that is often experienced by the public and employees is stress. Stress has the potential to encourage or interfere with the implementation work, depending on the level of stress experienced by the employees This research was conducted with the aim to see whether work related stress affects the performance of employees, with the object of the research, PT. Bank Perkreditan Rakyat Dana Manado. Employee Performance is measured by indicators of Quantity, Quality, and timeliness. In the fact stress can be helpful, improve and fun, but stress can also be damaging, threaten, worrisome, so stress has the potential to interfere the performance. The controlled population in this study is 50 people, while the number of samples taken in this study is 44 people. The collection of data used are questionnaires, interviews, and documentation. The data of the research, using simple regression, shows the influence of stress on the employees. The simple correlation test showed a strong negative correlation, meaning that both variables have an inverse relationship. If the X value is high, then the Y value will be low and vice versa. Based on the curve, the relationship of stress and performance of the employees of PT. Bank Perkreditan Rakyat Dana Raya is that before performance reaches a peak level, stress helps it grow to a higher level but when the levels of stress increases the employee’s performance began to decline and gradually become very low. From the results of the data analysis, the level of stress of the company has passed the maximum point because it is beginning to show a negative relationship. Suggestion in the reaserch is company must pay attention to the atmosphere around the office, create new innovations, and make a good personal communication within the company.Keyword: Work Stress, Performance Employees